FRI0383 Majority of us patients would not meet the proposed acr gout treatment guideline goal of SUA <6 mg/dl. (23rd January 2014) - Singh, J.; Hagerty, D.; Mischler, R.; Morlock, R.
Abstract : Background: Although gout is a relatively common condition, treatment is often not ideal with many patients continuing to experience multiple flares and some developing complications associated with the disease. To improve patient care the American College of Rheumatology (ACR) recently proposed a draft set of recommendations for treating patients with gout. Objectives: In a cohort of patients using a xanthine oxidase (XO) inhibitor therapy assess the percentage of patients that would meet the recently proposed treatment guidelines. Methods: Data were assessed from a quantitative survey of US physicians about gout disease management, oversampling for rheumatologists. Laboratory and clinical data were confirmed through chart audits using a structured case report form. The sample was restricted to patients treated with allopurinol or febuxostat. Type and initial allopurinol/febuxostat dose, presence of kidney disease, use of prophylactic medication, serum uric acid (sUA) level, physician type (rheumatologist vs. primary care physician [PCP]) and patient socio-demographics factors were identified. Descriptive statistics were used to describe the number of patients initiating ULT with prophylactic mediation, titration of allopurinol, having a follow-up sUA and achieving sUA ≤6 mg/dL within 12 months of treatment initiation. Results are presented overall and by physician type. Results: The sample included 125 rheumatologists and 124 PCPs. Of the 1245 patients with gout, 858 (69%) were treated with a XO inhibitor: 624 (72.4%) were treated with allopurinol and 247 (27.6%) were treated with febuxostat. Rheumatologists managed the care for 500 (58.3%) patients and PCPs managed the care for 358 (41.7%) patients. Rheumatologists used a prophylactic treatment (NSAIDs/colchicine/corticosteroids/Cox2s) in 67% of cases and only 37% of cases treated by PCPs had evidence of prophylactic therapy. A follow-up sUA assessment in the one-year following allopurinol/febuxostat initiation was done in 68% and 53% of patients managed by rheumatologists and PCPs, respectively. Rheumatologists were more likely to start with a lower dose of allopurinol (185mg) vs. PCPs (208mg) (p<0.01) and only 8% of patients treated by a PCP and 29% of patients treated by rheumatologists were titrated above 300mg of allopurinol (p<0.01). Within the 12 months of allopurinol/febuxostat treatment, only 50% of patients managed by rheumatologists and 36% of patients managed by PCPs achieved a sUA of ≤6 mg/dL (among those who had a sUA level checked). There was no statistically significant difference between allopurinol (45%) and febuxostat (41%) in the proportion of patients reaching sUA target (p=0.26). Conclusions: Adherence to draft ACR guidelines vary by physician type with no more than 50% of patients achieving sUA ≤6 mg/dL within 12 months of XO therapy. Significant opportunities exist to improve care for all patients regardless of physician specialty, including use of prophylactic treatment, increased dose titration and/or effective treatment strategies to bring patients to goal. Disclosure of Interest: J. Singh Grant/Research support from: Ardea Biosciences, Takeda, Savient, Consultant for: Takeda, Savient, Novartis, URL, D. Hagerty Employee of: Ardea Biosciences, R. Mischler Employee of: Ardea Biosciences, R. Morlock Employee of: Ardea Biosciences